Integration of Islamic Legal Values in the National Health Insurance Policy and Its Impact on Family Health - Marizem, Marizem; Yandi, Rus; Syahrizal, Syahrizal (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The government program related to the health insurance policy managed by BPJS Kesehatan is not only focused on health aspects but also has a significant impact on social and religious matters, particularly for the Muslim community in Indonesia. This policy program aligns with the fundamental principles of Islamic law, which aims to protect life, wealth, offspring, and so on, in order to achieve the welfare of the family. The purpose of this writing is to analyze the integration of Islamic law in the National Health Insurance (JKN) policy and its impact on the resilience of Muslim families. This research uses a qualitative method with a descriptive analysis approach. Data collection techniques were carried out through literature studies, followed by thematic analysis to identify the convergence points between Islamic values and the principles of JKN. The research findings show that the JKN policy accommodates Islamic legal values, such as the principle of ta’awun (mutual help). JKN directly contributes to the protection of life, intellect, wealth, and offspring through maternal and child health programs aimed at shielding families from catastrophic healthcare costs. The impact of this is seen in the resilience of families, with a reduction in financial pressure due to illness, improved health quality of family members, and the realization of a sense of security, which is a pillar of a peaceful, loving, and compassionate family (sakinah, mawaddah, warahmah).